Serum Protein Changes in Still's Disease, Rheumatoid Arthritis and Gout - Clarke, H. G. Minchin (1970)
Numerous workers have reported the electrophoretic changes in gout, rheumatoid arthritis and Still's disease. The recent introduction of an analytical technique capable of measuring discrete proteins rather than groups of proteins prompted a reassessment of the protein changes in these conditions. Eleven discrete α- and β-globulins were studied in all 3 conditions. All 3 showed statistically significant differences from normal values. The results obtained are discussed in relation to previous work and to the so called “acute phase reaction”.